Surface display of a functional single-chain Fv antibody on staphylococci. - Gunneriusson, E (1996)
Two different host-vector expression systems designed for cell surface display of chimeric receptors on Staphylococcus xylosus and Staphylococcus carnosus have been evaluated for surface display of a mouse immunoglobulin G1(kappa) [IgG1(kappa)] anti-human IgE single-chain Fv (scFv) antibody fragment. To achieve surface anchoring of the chimeric receptors containing the scFv, the cell surface attachment regions from Staphylococcus aureus protein A were used in both expression systems. The different chimeric receptors could be recovered from cell wall extracts of both S. xylosus and S. carnosus, and surface localization was demonstrated by taking advantage of a serum albumin-binding reporter region present within the two types of receptors. In addition, the two different recombinant staphylococci carrying hybrid receptors containing the scFv were demonstrated to react with the antigen, which was human IgE, in whole-cell enzyme-linked immunosorbent assays. This is the first report of an antibody fragment expressed in a functional form anchored to the surface of gram-positive bacteria. The potential use of recombinant gram-positive bacteria as whole-cell diagnostic devices or alternatives to filamentous phages for surface display of scFv libraries is discussed.